The Role of the Communicative Approach in the Development of Terminology - Campo, Ángela; Cormier, Monique (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe emergence of new terminology approaches does not mean that one approach should be used in preference to a previous one. These approaches suggest the structuring of terminology as a scientific research program, as described in Lakatos’s Methodology of Scientific Research Programmes. Specifically, we propose to explore the role of the Communicative Theory of Terminology in the development of the discipline. The heuristic of this approach, the set of rules intended to increase the probability of solving a problem within the discipline, will allow us to determine how the communicative approach contributes to the development of the research program.